Contabilidade governamental brasileira no contexto da convergência aos padrões internacionais - Greco, Marcus Vinicius Derito (2009)
With the globalization of the economy and the growing participation of several world investors in financial markets, combining the political, economical and social differences of each country, the varying Accounting Statements based on principles, standards, procedures or idiosyncratic accounting patterns become inadequate to provide comprehensible and useful financial information to the users at international level. Considering a country¿s conditions, peculiarities and the stage of development, the need to promote the convergence of the effective accounting practices in the public sector with the emerging international accounting standards is imperative as the public entities endeavor to provide transparent and comparable accounting information that can be understood by financial analysts, investors, auditors and other users, independent of their origin and location. Consequently, the objective of this research was described through the following questions: Which are the main differences between the international and local accounting norms applicable to the public sector in Brazil? Which are the main differences between the applicable international accounting norms and the practices adopted by the Brazilian public sector? And, which are the main differences between the practices adopted by the entities of the Brazilian public sector and the practices adopted by entities of the public sector of countries that formally follow the international accounting norms? The methodology adopted in this research was the one of comparative analysis between standards and practices. To provide a basis for the comparative analysis, the Brazilian standards were used for the public sector and the international standards were identified by consulting with the main international accounting committees. In the comparative analyses of norms adopted in national accounting statements the financial accounting statements of the Municipal districts of Rio de Janeiro and of São Paulo were used, and compared with the international accounting statements of New Zealand. The results of these comparative analyses provide important conclusions about the convergence and harmonization processes in accounting norms and practices for the public sector mainly as they demonstrate some of the conflicts among the recent efforts to base and harmonize accounting practices in the near future, but today significant differences remain between the norms and practices. It was also noticed that, in practice, the divergence in Brazilian accounting practices from the international standards are accentuated by the recognition of the registrations of the budgetary execution in the patrimonial accounting; and, the comparison with the practices adopted by New Zealand demonstrated that the foreign country¿s advances towards harmonizing its standards to the international norms and practices in such an important way that New Zealand independently overcomes the minimum exigencies of harmonization, which in practice, is more complete than the practices currently adopted in Brazil.